1974
DOI: 10.1128/iai.10.2.389-397.1974
|View full text |Cite
|
Sign up to set email alerts
|

Biological Properties of the Encapsulated Staphylococcus aureus M

Abstract: Strain M, classified as a Staphylococcus aureus, behaves like the other rare encapsulated staphylococcal strains. It was clumping-factor negative, grew in diffuse-type colonies in serum-soft agar, and produced rapidly fatal disease in mice. Strain M was highly resistant to phagocytosis by human or mouse leukocytes and required both specific antibody and heat-labile serum factor(s) for efficient ingestion by human polymorphonuclear leukocytes. Electron micrographs confirmed the presence of a large capsule. Aggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 23 publications
3
55
0
Order By: Relevance
“…Because of the large amount of capsule synthesized, strains producing type 1 or 2 capsule are mucoid on an agar surface, non-typeable with respect to phage, clumping-factor negative and exhibit a halo around the cells during negative staining with India ink. These strains have been shown to be antiphagocytic and virulent to mice (Lee et al, 1987;Melly et al, 1974;Peterson et al, 1978), although they are rarely isolated. In contrast, type 5 and 8 strains are the predominant isolates which account for approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the large amount of capsule synthesized, strains producing type 1 or 2 capsule are mucoid on an agar surface, non-typeable with respect to phage, clumping-factor negative and exhibit a halo around the cells during negative staining with India ink. These strains have been shown to be antiphagocytic and virulent to mice (Lee et al, 1987;Melly et al, 1974;Peterson et al, 1978), although they are rarely isolated. In contrast, type 5 and 8 strains are the predominant isolates which account for approx.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of taurine in the capsule is dependent on the presence of taurine in the growth medium (Wilkinson et al, 1979). The production of capsule in strain M has been correlated with its virulence properties in both in vitro phagocytic assays and in vivo mouse lethality assays (Melly et al, 1974;Peterson et al, 1978). It has been shown that the mechanism of resistance to opsonization is due to the masking of the bacterial surfacebound C3b complement by capsule, thus preventing interaction with the receptors on phagocytic cells by capsule.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm that Staphylococcus E-46 is highly resistant to phagocytosis (4, 5), probably because it is poorly opsonized. The capsule-like structure on the cell surface of Staphylococcus E-46 was initially postulated to confer resistance to phagocytosis (3)(4)(5) as reported for other encapsulated S. aureus (7,11,12). During storage of Staphylococcus E-46 on HI slants, the surface component seemed to change.…”
Section: Discussionmentioning
confidence: 88%
“…In some strains, cell surface components seem to contribute to the virulence. Encapsulated Staphylococcus aureus was reported to exhibit high virulence for mice, and it was shown that the presence of a polysaccharide capsule interferes with opsonization (7,11,12). M protein, the surface antigen of group A streptococci, is also known to participate in resistance to phagocytosis.…”
mentioning
confidence: 99%
“…Staphylococcus aureus, the pathogenic counterpart of CNS, can be encapsulated [4]. Such strains possessed increased virulence in comparison with their non-encapsulated variant strains [5,6]. Characterization of CNS has been advocated [7,8], but no special attention has been given to the presence of a capsule, although encapsulated CNS have been reported [9].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%